Familiarization, reliability, and evaluation of a multiple sprint running test using self-selected recovery periods - Glaister, M.; Witmer, C.; Clarke, D. W.; Guers, J. J.; Heller, J. L.; Moir, G. L. (The Journal of Strength and Conditioning Research, 2010)
The aims of the present study were to investigate the process of self-selected recovery in a multiple sprint test with a view to using self-selected recovery time as a means of reliably quantifying an individual's ability to resist fatigue in this type of exercise. Twenty physically active exercise science students (means ± SD for age, height, body mass, body fat, and VO2max of the subjects were 21 ± 2 yr, 1.79 ± 0.09 m, 83.7 ± 10.8 kg, 16.6 ± 3.9%, and 52.7 ± 7.2 ml/kg/min, respectively) completed 4 trials of a 12 × 30 m multiple sprint running test under the instruction that they should allow sufficient recovery time between sprints to enable maximal sprint performance to be maintained throughout each trial. Mean recovery times across the 4 trials were 73.9 ± 24.7, 82.3 ± 23.8, 77.6 ± 19.1, and 77.5 ± 13.9 seconds, respectively, with variability across the first 3 trials considered evidence of learning effects. Test-retest reliability across trials 3 to 4 revealed a good level of reliability as evidenced by a coefficient of variation of 11.1% (95% likely range: 8.0-18.1%) and an intraclass correlation coefficient of 0.76 (95% likely range: 0.40-0.91). Despite no change in sprint performance throughout the trials, ratings of perceived exertion increased progressively and significantly (p < 0.001) from a value of 10 ± 2 after sprint 3 to 14 ± 2 after sprint 12. The correlation between relative VO2max and mean recovery time was 0.14 (95% likely range: -0.37-0.58). The results of the present study show that after the completion of 2 familiarization trials, the ability to maintain sprinting performance in a series of repeated sprints can be self-regulated by an athlete to a high degree of accuracy without the need for external timepieces.